Tinjauan Yuridis terhadap Dispensasi Pernikahan Dibawah Umur dalam Perspektif Hukum Islam Indonesia - Ageng Subekti (LPPM STAI Muhammadiyah Probolinggo, 2024)
In Indonesia, the social phenomenon of underage marriage has difficulties in enforcing the law. This is related to the application for marriage through dispensation. Underage children should be protected and their rights and obligations as children should be fulfilled. So there needs to be synergy between the government, law enforcement, and the wider community in an effort to prevent child marriage at a young age for a better future for the next generation, this study uses a normative research method, In positive Indonesian law, the minimum age limit for marriage has been regulated in Article 7 paragraph 1 of Law No. 1 of 1974 concerning amendments to Law No. 16 of 2016 but there are still many people who violate these limits so that they apply for dispensation, In Islamic law a person can marry if they are considered baligh or an adult, Islam does not prohibit someone from marrying a minor if the person has reached baligh and meets various aspects such as physical, psychological and knowledge maturity as indicators of maturity in forming a household, the impact of early marriage dispensation has positive and negative impacts such as preventing free association and the negative impacts given are domestic violence, disharmony in the household which results in divorce Keywords: Dispensation, Early Childhood Marriage, Islamic Perspective, and Review of Law